2020
DOI: 10.1016/j.btre.2020.e00522
|View full text |Cite
|
Sign up to set email alerts
|

Optimization for enhanced ecofriendly decolorization and detoxification of Reactive Blue160 textile dye by Bacillus subtilis

Abstract: Highlights Bacillus firmus efficiently degrade and detoxified the textile dye of RB160 even at high concentrations within short duration. Induction of azoreductase, Liginperoxides and NADH–DCIP reductase activity in the strain to facilitate dye degradation process at the molecular level. The toxicity of the RB160 dye was degraded extremely after the biological treatment at specific condition. Bacterially degraded produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…For this purpose, different bacterial species and incubation conditions have been tested in decolorization of various dyes in many studies. Accordingly; in some of the studies in the literature, it is reported that higher decolorization rates were obtained in static conditions [20][21][22] and in others under shaking conditions [23][24][25]. This situation can be explained by the metabolic diversity of the tested bacterial species.…”
Section: Bacterial Dye Decolorizationmentioning
confidence: 98%
“…For this purpose, different bacterial species and incubation conditions have been tested in decolorization of various dyes in many studies. Accordingly; in some of the studies in the literature, it is reported that higher decolorization rates were obtained in static conditions [20][21][22] and in others under shaking conditions [23][24][25]. This situation can be explained by the metabolic diversity of the tested bacterial species.…”
Section: Bacterial Dye Decolorizationmentioning
confidence: 98%
“…In a comparably cost-efficient manner, the dyes are decomposed to a vast degree whilst less water is required and less sludge produced. The mechanisms of how microorganisms can decolorize (i.e., reduce azo bonds to aromatic amines) and degrade (i.e., break down azo dyes into small molecules leading to H 2 O, CO 2 , and mineral by-products) azo dyes have been a subject of interest in different studies [75][76][77][78][79][80]. Microbiological dye removal or even degradation can be achieved by means of various ways such as via adsorption, via the production of enzymes that can attack the dyes, and even via the combination of both [81,82].…”
Section: Biological Treatment Of Dyesmentioning
confidence: 99%
“…Along with heavy industrial pollutants, textile dyes are greatly toxic and potentially carcinogenic (Sharma et al, 2018) in nature and therefore, they are connected to the environmental pollution generating different diseases in humans and animals (Khan & Malik, 2018;Lellis et al, 2019). In the present time, microbial remediation of dyes wastes is a promising field of research and the mechanism behind microorganism-assisted decolorization or degradation of azo dyes have been a matter of interest in various studies (Akansha et al, 2019;Barathi et al, 2020;Dhir, 2022;Khan et al, 2013;Ngo & Tischler, 2022;Yang et al, 2022;Yesilada et al, 2018).…”
Section: Mycoremediation Of Dyesmentioning
confidence: 99%
“…Along with heavy industrial pollutants, textile dyes are greatly toxic and potentially carcinogenic (Sharma et al, 2018) in nature and therefore, they are connected to the environmental pollution generating different diseases in humans and animals (Khan & Malik, 2018; Lellis et al, 2019). In the present time, microbial remediation of dyes wastes is a promising field of research and the mechanism behind microorganism‐assisted decolorization or degradation of azo dyes have been a matter of interest in various studies (Akansha et al, 2019; Barathi et al, 2020; Dhir, 2022; Khan et al, 2013; Ngo & Tischler, 2022; Yang et al, 2022; Yesilada et al, 2018). Bacteria (Ghodake et al, 2011; Haque et al, 2021; Shah et al, 2013), filamentous fungi (Bhattacharya et al, 2011; Singh & Pakshirajan, 2010), yeasts (Dias et al, 2010; Ngo et al, 2016), and algae (El‐Sheekh et al, 2021; Shetty & Krishnakumar, 2020) are the microorganisms which have ability to degrade or decolorize the dyes molecules (Ngo & Tischler, 2022).…”
Section: Mycoremediation Of Organic Pollutantsmentioning
confidence: 99%